Fungal community assembly in drought-stressed sorghum shows stochasticity, selection, and universal ecological dynamics - Cheng Gao (Nature Portfolio, 2020)
Fungal community assembly on crop plants is thought to be driven by deterministic selection exerted by the host. Here Gao et al. use a sorghum system to show that stochastic forces act on fungal community assembly in leaves and roots early in host development and when sorghum is drought stressed.